DETECTION SYSTEM OF OPTICAL LIGHTING HAZARDS TO RECEIVE THE RAYLEIGH HOLIDAYS COMPARED TO THE CONVENTIONAL SYSTEM - Suparno Suparno (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2002)
mode fibre optics of 4.6pm diameter and a quarter pitch rens has been coupled by the use of SF connector and stainless housing to produce a very reliable light transducer. The ltIII'SdulCeirs capable of transmitting light thousands times compared of using fibre optics only. Besides its ability in transmittingit has some other advantages such as small dimension and relatively cheap cost of production. The reliability of the transducer ill transmitting light was tested to observe scattered light from very JlnQIIparticles of toluene known as Rayleigh scattering.